Urban studies and fractal geometry - Palma, Niara (2017)
Conventional methodologies in the study of urban form have not been considering the whole morphological complexity of cities or the degree of irregularity of urban perimeters as they address the physical form of cities within the scope of Euclidean geometry. This paper explores the application of fractal geometry in the study of urban areas, focusing on a number of aspects of physical form related to the fragmentation of urban fabrics, the presence of urban voids and, finally, the existence of self-similarity at different scales of observation. This analysis draws on the research work developed by Frankhauser from the 1990s onwards. Fractal analysis is applied to a set of five cities in the Vale do Rio Pardo, Rio Grande do Sul, Brazil. Over the last years, this set of cities had an uncontrolled pattern of growth. The rapid urban development patterns and the expansion of urban perimeters have led to a type of rarefied territorial occupation with major impacts on the urban fabrics of these cities.